2015
DOI: 10.1001/jamaoto.2014.3581
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gastric Pepsin in the Inflammatory Cascade of Pediatric Otitis Media

Abstract: Extraesophageal reflux as indicated by the presence of pepsin A is closely involved in the middle ear inflammatory process and may worsen the disease in some children; however, a proof of cause and effect between extraesophageal reflux and middle ear inflammation requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 47 publications
3
49
2
3
Order By: Relevance
“…However, during weak and nonacid reflux commonly experienced by patients taking PPIs, the enzymatic activity of pepsin is transiently inhibited, allowing interaction with an unidentified cell surface receptor, endocytosis, and retention in acidic intracellular vesicles where its enzymatic activity would be restored . Pepsin has been observed in a variety of airway and esophageal epithelial cells where it initiates a cascade of inflammation and cancer‐associated changes . We previously demonstrated that <24‐hour pepsin exposure induces a cancer‐promoting gene expression profile, anchorage‐independent growth, and cell migration in hypopharyngeal and laryngeal cells in vitro, and that pepsin promoted oral tumor growth in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, during weak and nonacid reflux commonly experienced by patients taking PPIs, the enzymatic activity of pepsin is transiently inhibited, allowing interaction with an unidentified cell surface receptor, endocytosis, and retention in acidic intracellular vesicles where its enzymatic activity would be restored . Pepsin has been observed in a variety of airway and esophageal epithelial cells where it initiates a cascade of inflammation and cancer‐associated changes . We previously demonstrated that <24‐hour pepsin exposure induces a cancer‐promoting gene expression profile, anchorage‐independent growth, and cell migration in hypopharyngeal and laryngeal cells in vitro, and that pepsin promoted oral tumor growth in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The gastric enzyme pepsin has previously been shown to promote chronic inflammation and carcinogenesis in the upper airways during extraesophageal reflux, which is typically weak or nonacidic and similar to that of patients taking PPIs . Furthermore, parietal and chief cells observed in BE, in the background of EAC and in heterotopic gastric mucosa patches in the esophagus, represent a potential source of locally synthesized pepsin and acid that may contribute to disease progression .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Host factors that increase the risk of OM include: young age 32 , male sex 33 , race and ethnicity 33 , genetic factors and a family history of OM 34 , craniofacial anomaly such as cleft palate 35 , atopy 34 , immunodeficiency 36 , upper respiratory tract infections (URTIs) and adenoid hypertrophy 34,37 , and laryngopharyngeal reflux 38 . Environmental factors that increase the risk of OM include: low socioeconomic status, exposure to tobacco smoke 34 , having older siblings 39 , day-care attendance 32,39,40 and the use of a pacifier 41,42 .…”
Section: Social and Environmental Risk Factorsmentioning
confidence: 99%
“…However, little is known about the esophageal reflux symptoms these children do or do not present, the results of reflux tests in those without pepsin in the middle air fluid, the long-term outcome and the impact of reflux therapy. A proof of cause and effect between extra-esophageal reflux and middle ear inflammation is still missing [59].…”
Section: Ger(d) and Other Manifestationsmentioning
confidence: 99%